2020
DOI: 10.36956/sms.v1i2.94
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition and Anticancer Effect of Different Seaweed Species (In-vitro and In-vivo Studies)

Abstract: Seaweed is an enormous resource comprised with natural bioactive compounds comprise with several therapeutic effects including anticancer activity. In this context, the biochemical composition of seaweeds plays a major role. Many biochemical compounds extracted from seaweeds and crude extracts, such as aqueous, methanolic account mainly for the anticancer effect against several cancer cell line. In this contrast seaweed extracts inhibit cancer cell growth and proliferation by inducing apoptosis and inhibit met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Seaweeds have been known to contain bioactive compounds 5 that are derived from sulfated polysaccharides, polyphenols, carotenoids, proteins and lipids 6 . Seaweeds have demonstrated anti-inflammatory 7 , wound healing 8 , 9 , anti-cancer 10 , anti-diabetic activities, and anti-degenerative activities 6 . Isolated compounds of seaweeds have been subjected to clinical trials to investigate their potential drug abilities in the field of oncology 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds have been known to contain bioactive compounds 5 that are derived from sulfated polysaccharides, polyphenols, carotenoids, proteins and lipids 6 . Seaweeds have demonstrated anti-inflammatory 7 , wound healing 8 , 9 , anti-cancer 10 , anti-diabetic activities, and anti-degenerative activities 6 . Isolated compounds of seaweeds have been subjected to clinical trials to investigate their potential drug abilities in the field of oncology 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a wide range of anti-inflammatory, antibiotic, anti-HIV, anticoagulant, anticonvulsant [ 10 ], antineoplastic, antiulcer [ 11 ], and antimicrobial activities of seaweeds have also been reported [ 12 ]. Also, seaweeds are comprised of bioactive compounds that are capable of producing a great variety of secondary metabolites with broad biological activities [ 13 , 14 ]. The seaweeds can also be used to prevent tissue damage and stimulate the wound healing process [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Docking is habitually utilized for evaluating the binding between the ligand and the receptor 23 . However, the previous studies indicated the antibacterial, antioxidant and anti-cancerous properties of this seaweed in the ethanol extract [24][25][26] but the present study aimed at determining numerous phytochemical compounds responsible for breast cancer through insilico methods. It is well-known that mutated domains are accountable for the cancer progression, and rendering to the Database of Cancer Mutant proteins database(DCMP) BRCA1 C-terminal (BRCT) domains are vital signalling elements in the DNA damage response.…”
Section: Introductionmentioning
confidence: 96%